Financial education and its impact on the personal finances of teachers at a Peruvian educational institution - Flores Lezama, Marilú Trinidad; Bazán Sánchez, Irma; Rosero Sandoval, Winnie Karina; Quispe Silva, Maryxandra Yamile; Zambrano Vásquez, Nayheli Yazmin (LACCEI, 2023)
The present research entitled "Financial education and its impact on the personal finances of the teachers of educational institution", had the objective of knowing the impact between the two mentioned variables of financial education to improve personal finances, it was of non-experimental design, because it was established without modifying the variables and the data collected served to be observed and distinguished. Likewise, it was cross-sectional because it was elaborated in a single time. In addition, it had a quantitative approach with a correlational level because it proposes the validity of a relationship between variables, for which a population and sample of 45 teachers were taken, to whom a survey was applied, with a total of 28 questions, which were later processed in statistical programs, obtaining as results that the vast majority of teachers did not know how to adequately plan their income, also their credit situation was regular, they do not adequately manage their budget and many of them did not have saving habits.